Mitigating surface vortex formation in pump sump intakes through anti-vortex devices: a comprehensive CFD study - Alaboodi, Abdulaziz S.; Hussain, Zahid; Abbas, Saqlain; Rehman, Masood ur; Zulfiqar, Asim (Frontiers in Physics, 2024)
The formation of surface vortices in axial pump sumps presents a significant challenge to pump performance, primarily due to the risk of impeller cavitation. As such, effective mitigation strategies are imperative. In this study, the strength of surface vortices was successfully reduced to a safe operational level by employing two distinct types of anti-vortex devices (AVDs): triangular side fins type (AVDSF) and ring type (AVDR). Computational fluid dynamics (CFD) techniques were employed to reveal a substantial decrease in surface vorticity from 38 s-1 in the absence of AVDs to approximately 8 s-1 with either AVDSFs or AVDRs, underscoring their remarkable efficacy. Further, the helicity, a measure of vortex twisting, was reduced from about 0.4 m2s-2 to below 0.1 m2s-2 with the introduction of either side fins or ring-type AVDs. Detailed analyses of velocity streamlines contours elucidated that the suppression of surface vortices could be attributed to the disruption of vortex swirl motion induced by the implementation of AVDs. These findings provide crucial insights into the mechanisms underlying surface vortex suppression, thus paving the way for enhanced pump performance and reliability in axial pump’s suction sump applications. The implementation of AVDs is expected to prevent cavitation, air ingress, and vortex-induced vibrations, resulting in more reliable and efficient pump operation in industrial settings.